Ultraconserved elements in the human genome: association and transmission analyses of highly constrained single-nucleotide polymorphisms. - Chiang, Charleston W K; Liu, Ching-Ti; Lettre, Guillaume; Lange, Leslie A; Jorgensen, Neal W; Keating, Brendan J; Vedantam, Sailaja; Nock, Nora L; Franceschini, Nora; Reiner, Alex P; Demerath, Ellen W; Boerwinkle, Eric; et al. (Genetics, 2012)
Ultraconserved elements in the human genome likely harbor important biological functions as they are dosage sensitive and are able to direct tissue-specific expression. Because they are under purifying selection, variants in these elements may have a lower frequency in the population but a higher likelihood of association with complex traits. We tested a set of highly constrained SNPs (hcSNPs) distributed genome-wide among ultraconserved and nearly ultraconserved elements for association with seven traits related to reproductive (age at natural menopause, number of children, age at first child, and age at last child) and overall [longevity, body mass index (BMI), and height] fitness. Using up to 24,047 European-American samples from the National Heart, Lung, and Blood Institute Candidate Gene Association Resource (CARe), we observed an excess of associations with BMI and height. In an independent replication panel the most strongly associated SNPs showed an 8.4-fold enrichment of associations at the nominal level, including three variants in previously identified loci and one in a locus (DENND1A) previously shown to be associated with polycystic ovary syndrome. Finally, using 1430 family trios, we showed that the transmissions from heterozygous parents to offspring of the derived alleles of rare (frequency ≤ 0.5%) hcSNPs are not biased, particularly after adjusting for the rates of genotype missingness and error in the data. The lack of transmission bias ruled out an immediately and strongly deleterious effect due to the rare derived alleles, consistent with the observation that mice homozygous for the deletion of ultraconserved elements showed no overt phenotype. Our study also illustrated the importance of carefully modeling potential technical confounders when analyzing genotype data of rare variants.
Keywords: Alleles; Animals; Body Height; Body Mass Index; Child; Conserved Sequence; Dogs; Evolution, Molecular; Female; Genetic Fitness; Genetic Variation; Genome, Human; Genotype; Humans; Inheritance Patterns; Male; Mice; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Rats; Reproduction; Young Adult